Pseudoexfoliative glaucoma: clinical signs (Ukrainian Journal of Ophthalmology, 2025)
Background: Knowing characteristic clinical signs of pseudoexfoliative glaucoma (PEG) is important for a practicing ophthalmologist because it would allow early detection of a particularly severe form of glaucomatous process in the presence of pseudoexfoliative syndrome (PXS). PEG accounts for 25%-30% of all open-angle glaucoma cases. Most patients with PXS undergo cataract surgery with undiagnosed PEG, and, in these cases, glaucoma is late detected and misclassified as conventional open-angle glaucoma.Purpose: To determine characteristic clinical PEG signs that could be used as diagnostic aids.Material and Methods: One hundred and fourteen patients (146 eyes; age, 59 to 90 years; mean age, 74.73 ± 0.50 years) with PXS were included in the study. Patients underwent visual acuity assessment, biomicroscopy, gonioscopy, static automated perimetry, and SD OCT (Topcon 3D OCT-2000FA Plus; version 7/21/003/0) using 3D Macula, 3D Disc and 3D (V) Glaucoma Analysis in the Macula 3D (V) over a 7.0x7.0-mm scan area.Results: Signs of the presence of PXS with deposits of exfoliation material in various anterior segment structures were identified in study patients. High intraocular pressure (IOP) levels ranging from 29 mmHg to 34 mmHg were characteristic for the patients with a narrowed or closed anterior chamber angle, increased pigmentation and/or exfoliative conglomerates. Patients with small granular or lace-like exfoliations had an IOP of 22-28 mmHg. Static perimetry showed specific changes in the visual field like a diffuse reduction of MD (48.2% of eyes), expanded blind spot (5.5%), paracentral scotoma (4.0%), nasal step defect (5.5%), focal non-specific defects (13.2%) and concentric visual field narrowing (23.6%). OCT showed thinned NFL (33.60 ± 0.43 in eyes with PXS even without increased IOP, with a mean cup-disc ratio of 0.49 ± 0.04, and  a significantly thinned NFL of 28.80±0.42 in eyes with PEG) and NFL+GCL+IPL (98.80±0.43 in eyes with PXS and 84.0±1.87 in PEG). In addition, OCT showed significant inferior, temporal, nasal and total RNFL thinning in eyes with PXS, and even more substantial thinning, in eyes with PEG. This indicated less apparent not only macular but also diffuse peripapillary retinal thinning. Moreover, the retinal thickness values for eyes with PXS were close to those characterizing the presence of glaucomatous process in eyes with open-angle glaucoma.Conclusion: The presence of pseudoexfoliative syndrome is a factor with the threat of PEG (26% of patients with PXS were found to have PEG). The 24-hour IOP curve was characterized by higher IOP values in the morning hours for 28.8% of eyes with PEG, or the late evening and early morning hours, with normal IOP values in the day hours for 71.2% of eyes with PEG. This makes specific monitoring relevant. Retinal NFL and RNFL thickness monitoring in eyes with PXS may contribute to early identification of eyes at risk for PEG.
Keywords: pseudoexfoliative syndrome; pseudoexfoliative glaucoma